Corona aging resistant environment-friendly motor and manufacturing method thereof

By using insulating materials composed of nanoscale MPIA staple fibers and nanotitanium dioxide particles in the motor, combined with specific insulating structures, the problems of corona aging and recycling are solved, and efficient and environmentally friendly insulation performance is improved.

CN119891612AActive Publication Date: 2025-04-25NORTH CHINA ELECTRIC POWER UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510368428.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

Existing motor insulating materials are prone to corona aging in high voltage environments, resulting in a decrease in insulation strength and an increase in breakdown risk, and recycling is difficult to achieve.

Method used

The insulating material consisting of nanoscale MPIA staple fibers and nanotitanium dioxide particles is used to combine specific insulating structures to improve insulation performance and environmental protection.

Benefits of technology

The synchronous improvement of insulation performance and environmental protection level has been achieved, the anti-corona aging ability has been significantly enhanced, the materials can be recycled and reused, the recycling cycle is short and the quality recovery rate is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119891612A_ABST
    Figure CN119891612A_ABST
Patent Text Reader

Abstract

The invention provides an anti-corona aging environment-friendly motor and a manufacturing method thereof, the environment-friendly motor comprises a stator core and a stator winding, the stator core is provided with a stator slot for placing the stator winding, the stator core is formed by laminating a plurality of silicon steel sheets, and the silicon steel sheets are arranged in the stator slot. The stator slots are internally provided with insulation structures made of recoverable corona-resistant insulation materials, the insulation structures comprise slot body insulators and inter-winding insulators, the slot body insulators are laid on the inner walls of the stator slots, the inter-winding insulators are arranged in a space defined by the stator slots, the space defined by the stator slots is divided into a plurality of parts in the cross section direction of the stator core, and the insulation structures are arranged in the slot body insulators. Stator windings wound in the stator slots are separated; the insulating material comprises nano-scale MPIA short fibers and nano titanium dioxide particles. The environment-friendly motor not only has excellent corona aging resistance, but also has the characteristic of recoverability, the manufacturing process is simple, the recovery path is green and environment-friendly, and the environment-friendly motor has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of motors, and more specifically, relates to an environmentally friendly motor that is resistant to corona aging and a manufacturing method thereof. Background Art

[0002] The insulating material used to manufacture the motor insulation structure should have good insulation performance and mechanical strength. In the prior art, although the insulating material has been industrialized, it has the defects of insufficient insulation strength, short service life, and difficulty in recycling.

[0003] Insulating materials used in motors in the prior art generally serve in high voltage environments. In addition to the risk of electrical breakdown, the influence of long-term strong electric fields will also cause varying degrees of aging on the surface and inside of the material, mainly in the form of thermal aging and corona aging. Corona aging will cause powdering and cracking on the surface of the material, and the internal structure will also become loose, reducing the insulation strength of the material and increasing the risk of breakdown.

[0004] Specifically, corona aging affects materials in three main ways: (1) the impact of high-energy particles may break chemical bonds with lower bond energy on the surface of the material, changing the surface morphology and roughness; (2) chemical corrosion of active products, such as ozone, can accelerate the degradation of the insulating surface; (3) thermal effect. Corona discharge will produce a strong thermal effect, which will continuously cause thermal aging of the material and cause changes in its internal structure.

[0005] At the same time, the application of recyclable materials and the exploration of recycling paths for insulating materials have always been the focus of attention in the industry. In addition to traditional landfill and incineration, there are two main ways to deal with insulating materials: physical recycling and chemical recycling. Physical recycling includes cleaning, crushing, melting, granulation, etc. Its recycling efficiency is low and it is impossible to maximize the utilization of aging and scrapped materials. Chemical recycling methods are generally high-temperature degradation under extreme conditions. A method of recycling insulating substrates using subcritical water and supercritical water in the prior art has extremely high energy consumption and a long recycling cycle, and it is impossible to achieve large-scale green recycling. Summary of the invention

[0006] In order to solve the deficiencies in the prior art, the present invention provides an environmentally friendly motor that is resistant to corona aging and a manufacturing method thereof, which adopts an insulation structure with a specific structure and specific materials to achieve simultaneous improvement of insulation performance and environmental protection level.

[0007] The present invention adopts the following technical solution.

[0008] A first aspect of the present invention provides an environmentally friendly motor that is resistant to corona aging, comprising: a stator core and a stator winding, wherein the stator core is provided with stator slots for accommodating the stator winding; The stator core is made of multiple silicon steel sheets stacked together, and the stator winding is placed in the slots of the stator core. An insulation structure made of recyclable anti-corona insulation material is arranged in the stator slot, and the insulation structure includes: slot body insulation and inter-winding insulation, the slot body insulation is laid on the inner wall of the stator slot, and the inter-winding insulation is arranged in the space surrounded by the stator slot, and the space surrounded by the stator slot is divided into multiple parts in the direction of the cross section of the stator core, so as to separate the stator windings wound in the stator slot; The insulating material comprises: nano-scale MPIA short fibers and nano-titanium dioxide particles.

[0009] Preferably, the stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot opening. The slot body insulation is consistent with the shape of the inner wall of the stator slot and extends toward the center of the slot opening at the slot opening. The inter-winding insulation includes a longitudinal beam and a cross beam extending from the longitudinal beam to both sides. The cross beam at the bottom of the slot is arc-shaped and abuts against the slot body insulation at the bottom of the slot. The cross beam at the slot opening closes the slot opening and overlaps with the slot body insulation at the slot opening.

[0010] Preferably, nano-sized MPIA staple fibers and nano-titanium dioxide particles, wherein the nano-sized MPIA staple fibers are prepared by deprotonating the MPIA staple fibers in a DMAc / LiCl system, and have a diameter of 7-10 nanometers; The nano-titanium dioxide particles are rutile crystal type, have a particle size of 5-20 nanometers, a mass fraction of 10-20 wt%, and are uniformly distributed in the nano-scale MPIA staple fibers.

[0011] Preferably, the surface of the slot insulation and the inter-winding insulation is smooth and pure white, with a thickness of 0.08-0.20 mm, and the interface is a honeycomb porous structure with a hole diameter of 0.5-1 nm; After aging in a strong DC electric field for 20-40 hours, the breakdown field strength and tensile strength of the slot insulation and the insulation between the windings still retain 90-95% of the original state, and the dielectric constant and dielectric loss remain at 94-98% of the existing technical state.

[0012] A second aspect of the present invention provides a method for manufacturing an environmentally friendly motor that is resistant to corona aging, which is used to manufacture the environmentally friendly motor that is resistant to corona aging, comprising the following steps: A stator core including a stator slot structure is manufactured using magnetic material; An insulating material comprising nano-scale MPIA staple fibers and nano-titanium dioxide particles is prepared, and slot insulation and inter-winding insulation are prepared based on the insulating material; Insert the prepared slot insulation into the stator slot, ensuring that the insulation paper completely covers the slot wall and leaves a margin; insert interwinding insulation between different layers of the winding to prevent short circuits between layers; Install the rotor core, permanent magnets or windings, perform dynamic balancing tests, and install other accessory structures to complete the assembly.

[0013] Preferably, the method of manufacturing a stator core including a stator slot structure using a magnetic material comprises: A punching machine is used to punch the silicon steel sheet into a ring having a stator slot structure, and then annealing is performed, wherein the stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot opening; Coating a layer of insulating material on the surface of the silicon steel sheet; The punched silicon steel sheets are stacked together according to the design requirements; the outer circle and inner hole of the stator core are turned, and the burrs generated during the punching and processing are removed.

[0014] Preferably, the preparation of the insulating material comprising nano-scale MPIA staple fibers and nano-titanium dioxide particle components, and the preparation of slot insulation and inter-winding insulation based on the insulating material respectively comprises: The MPIA staple fibers were placed in a DMAc / LiCl system and deprotonated at a set temperature to form an ANF solution; Grind the nano-titanium dioxide particles, add the ground particles into the ANF solution and stir mechanically to form ANF / mixture; The obtained ANF / The mixture is applied on the coating machine to set the coating thickness Coating film; The resulting ANF / Aerogel is dried at a set temperature and drying time Drying is carried out and the hot pressing temperature is set , hot pressing pressure and heat pressing time Applying heat pressing; The hot-pressed insulating material is cut according to the stator slot type, winding size and insulation requirements of the motor to prepare slot body insulation and inter-winding insulation.

[0015] Preferably, the hot-pressed insulating material is cut according to the stator slot type, winding size and insulation requirements of the motor to prepare the slot body insulation and inter-winding insulation, which includes: The slot body insulation is prepared to be consistent with the shape of the inner wall of the stator slot, and extends to the center of the slot at the slot opening. The insulation between the windings includes a longitudinal beam and a cross beam extending from the longitudinal beam to both sides. The cross beam at the bottom of the slot is arc-shaped and presses against the slot body insulation at the bottom of the slot. The cross beam at the slot opening closes the slot and overlaps with the slot body insulation at the slot opening.

[0016] Preferably, the deprotonation temperature 130-150℃, time For 6-10 hours, the concentration of LiCl The concentration of ANF is 0.02-0.04 g / mL. 0.06-0.08 g / mL; Nano titanium dioxide particles are rutile crystals, and the particle size of nano titanium dioxide is 5-20 nanometers, mass fraction 10-20 wt%, mechanical stirring time 0.5-1 hour.

[0017] Coating thickness 0.8-1.2 mm, size 10 cm × 15 cm; Standing time in deionized water 10-15 hours; Drying temperature 60-100℃, drying time 0.5-1 hour, hot pressing temperature 160-200℃, hot pressing pressure 15-20 MPa, hot pressing time 1-2 minutes, thickness after hot pressing 0.08-0.2 mm.

[0018] Preferably, the step of placing the MPIA staple fibers in a DMAc / LiCl system to deprotonate at a set temperature to form an ANF solution comprises: The insulation structure of the recycled environmentally friendly motor is crushed and separated, and the metal impurities in the insulation structure are separated by screening, magnetic separation and other methods to obtain MPIA short fibers for deprotonation to form an ANF solution.

[0019] Compared with the prior art, the beneficial effects of the present invention include at least: the present invention adopts an insulating structure with a specific structure and specific material to manufacture an environmentally friendly motor that is resistant to corona aging, achieving a simultaneous improvement in insulation performance and environmental protection level; specifically, the insulating material not only has excellent anti-corona aging ability, but also has the characteristic of being recyclable, with a simple preparation process and a green and environmentally friendly recycling method, and has good application prospects. In addition to being used as an insulating component in motors, the technical solution provided by the present invention can also be horizontally expanded to other power equipment as an insulating component that undertakes electrical insulation, mechanical support and heat dissipation, thereby improving the anti-corona aging performance and environmental protection level of these power equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A schematic diagram of a stator of an environmentally friendly motor that is resistant to corona aging provided by the present invention; Figure 2A schematic diagram of the insulation structure of an environmentally friendly motor that is resistant to corona aging provided by the present invention; Figure 3 The present invention provides a flow chart of a method for preparing an insulating material used in an insulating structure of an environmentally friendly motor that is resistant to corona aging. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The described embodiments are only embodiments of a part of the present invention, not all embodiments. Based on the spirit of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.

[0022] like Figure 1 As shown, embodiment 1 of the present invention provides an environmentally friendly motor that is resistant to corona aging, including: a stator core 10 and a stator winding. The stator core is provided with stator slots 20 for accommodating the stator winding 30.

[0023] The stator core is the main part of the stator, preferably but not limited to, composed of multiple thin silicon steel sheets stacked together. Silicon steel sheets have low magnetic resistance and high resistivity, which can reduce eddy current losses. These silicon steel sheets are bonded together by an insulating agent to form a solid whole to support the mechanical structure of the stator and serve as a path for magnetic flux.

[0024] The stator winding is a coil placed in the slots of the stator core. The stator winding generates a magnetic field through the current, which interacts with the magnetic field of the rotor to generate torque. The stator winding can be, for example but not limited to, loose-embedded or fully-embedded, depending on the type and design of the motor.

[0025] As one of the outstanding essential features of the present invention, an insulating structure made of recyclable anti-corona insulating material is provided in the stator slot, such as Figure 2 As shown, the insulation structure includes: slot body insulation 40 and inter-winding insulation 50, the slot body insulation is laid on the inner wall of the stator slot, and the inter-winding insulation is arranged in the space surrounded by the stator slot, and the space surrounded by the stator slot is divided into multiple parts in the cross-section direction of the stator core, and the stator windings wound in the stator slot are separated. In combination with the insulation structure, the slot body insulation and the inter-winding insulation use the same insulating material, and the insulating material contains: nano-scale MPIA staple fibers and nano-titanium dioxide particles.

[0026] Preferably, but not limiting, such as Figure 2As shown, the stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot opening. The slot body insulation is consistent with the shape of the inner wall of the stator slot and extends to the center of the slot opening at the slot opening. The inter-winding insulation includes a longitudinal beam and a cross beam extending from the longitudinal beam to both sides. The cross beam at the bottom of the slot is arc-shaped and presses against the slot body insulation at the bottom of the slot. The cross beam at the slot opening closes the slot opening and overlaps with the slot body insulation at the slot opening.

[0027] It is worth noting that, as one of the outstanding substantive features of the present invention and a significant improvement over the prior art, the present invention provides an insulating material that is resistant to corona aging and recyclable, combined with a specific insulating structure, so that the motor's anti-corona aging performance is significantly improved, and the insulating material is a renewable material, and when the motor's life cycle ends or the insulating structure is updated, the insulating material can be recycled and reused. In other words, the present invention simultaneously achieves the improvement of the motor's insulation performance and environmental protection level.

[0028] Specifically, the insulating materials used to prepare slot insulation and inter-winding insulation include: nano-scale MPIA staple fibers and nano-titanium dioxide particles, wherein the nano-scale MPIA staple fibers are prepared by deprotonating the MPIA staple fibers in a DMAc / LiCl system, and have a diameter of 7-10 nanometers. The nano-titanium dioxide particles are rutile crystals, have a particle size of 5-20 nanometers, and a mass fraction of 10-20 wt%, and are evenly distributed in the nano-scale MPIA staple fibers.

[0029] The surface of the insulating material is smooth and pure white, with a thickness of 0.08-0.20 mm, a honeycomb porous structure at the interface, and a hole diameter of about 0.5-1 nanometer. It has a strong ability to resist corona aging. After aging in a strong DC electric field for 20-40 hours, its parameters such as breakdown field strength and tensile strength remain at 90-95% of the existing technical state, and the dielectric constant and dielectric loss remain at 94-98% of the existing technical state.

[0030] When recycling motor parts, the slot insulation and inter-winding insulation prepared from the insulating material can be deprotonated again in a DMAc / LiCl system to form ANF / Suspension, thus achieving green and efficient chemical recycling. The recycling cycle is 20-30 hours, and the mass recovery rate is as high as 92-97%. The insulation performance, mechanical properties, and dielectric properties of the recycled insulation material can fully retain the existing technical level.

[0031] It is worth noting that in the prior art, a bending-resistant composite mica tape is used to prepare an insulating structure in the motor, but the total thickness of the bending-resistant composite mica tape is 0.8-1.5 mm. Too high a thickness may affect its heat dissipation performance and service life. The base material used is a micron structure, which limits the insulation strength and mechanical strength. In the present invention, the prepared MPIA insulating material has a thickness of 0.08-0.2 mm, has excellent heat dissipation performance and anti-aging ability provided by the embodiment of the present invention, and ensures its service life. The uniform and dense nanostructure ensures that the prepared theater structure has excellent insulation strength and mechanical strength.

[0032] Embodiment 2 of the present invention provides a method for manufacturing a corona aging resistant and environment-friendly motor as described in Embodiment 1, comprising the following steps: Step 1: A stator core including a stator slot structure is manufactured using magnetic materials.

[0033] Preferably but not limiting, step 1 specifically comprises: Step 1.1: Use a precision punch to punch silicon steel sheets with high magnetic permeability, low iron loss and good mechanical properties into a ring with a stator slot structure, and perform annealing to eliminate internal stress and improve magnetic properties. Among them, the stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot mouth.

[0034] Step 1.2: Coat a layer of insulating material on the surface of the silicon steel sheet, preferably but not limited to phosphate or organic coating, to reduce eddy current loss.

[0035] Step 1.3: Use a hydraulic press or mechanical press to stack the punched silicon steel sheets according to the design requirements; turn the outer circle and inner hole of the stator core to ensure dimensional accuracy and surface finish; remove burrs generated during punching and processing to avoid affecting the motor performance.

[0036] Step 2: Prepare an insulating material comprising nano-scale MPIA staple fibers and nano-titanium dioxide particle components, and prepare slot insulation and inter-winding insulation based on the insulating material.

[0037] Preferably, but not limiting, such as Figure 3 As shown, step 2 specifically includes: Step 2.1: MPIA (Poly-m-phenylene isophthalamide) staple fibers are placed in a DMAc / LiCl system and deprotonated at a set temperature to form an ANF (Aramid NanoFiber) solution.

[0038] Further preferably but not limiting, in step 2.1, the deprotonation temperature is 130-150°C, deprotonation time For 6-10 hours, the concentration of LiCl The concentration of ANF is 0.02-0.04 g / mL. More preferably, the deprotonation temperature 140-145°C, deprotonation time For 8-10 hours, the concentration of LiCl The concentration of ANF is 0.027-0.035 g / mL. It is 0.067-0.075 g / mL.

[0039] It is worth noting that the present invention first recognizes that MPIA material is a polymer material with excellent thermal stability, excellent insulation strength, and super mechanical strength, and has broad application prospects in the insulation application of environmentally friendly motors. At the same time, MPIA staple fibers have the ability to be deprotonated into nanoscale MPIA in the DMAc / LiCl system, which not only creates favorable conditions for the incorporation of inorganic fillers with different characteristics, but also creates the possibility of efficient and green chemical recycling of MPIA-based materials. If MPIA materials can be used in the preparation of insulating materials, a high-performance insulating material that can be flexibly modified and recyclable can be provided, and the application of this material in motors will have great competitiveness.

[0040] Also, because the MPIA staple fibers have the ability to be deprotonated into nano-scale MPIA staple fibers in the DMAc / LiCl system, the deprotonated ANF solution can be regenerated in deionized water, reshape the physical structure, and restore the insulation capacity, providing a reliable path for energy-saving chemical closed-loop recycling. On this basis, the present invention performs anti-corona aging modification, and the provided recyclable and anti-corona aging environmentally friendly motor has greater application potential.

[0041] On the one hand, in the prior art, organic solvents such as DMSO (DimethylSulfoxide) and DMF (Dimethylformamide) are used to dissolve, process or modify the insulating materials in the manufacturing and processing of motor insulating materials, usually in combination with other chloride salts, but it is difficult to fully deprotonate the surface of the insulating materials. As one of the outstanding substantive features of the present invention, the DMAc / LiCl system is used for deprotonation at 140°C, so that the MPIA staple fibers are fully deprotonated into uniform nanoscale MPIA staple fibers. The insulating materials produced have a dense and uniform nanostructure, which ensures excellent mechanical strength and insulation strength in the motor stator.

[0042] On the other hand, in the prior art, the insulation structure of the motor is prepared by using micron-structured MPIA insulation material, but the internal pores of the micron structure are large and unevenly distributed, resulting in uneven distribution of inorganic fillers. The base material of the present invention is a nanostructure, prepared by deprotonating MPIA short fibers at 140°C in a DMAc / LiCl system, and has few internal pores. The interface of the prepared insulation material is a honeycomb porous structure with a pore diameter of About 0.5-1 nanometer.

[0043] Step 2.2: Grind the nano-titanium dioxide particles, add the ground particles into the ANF solution and stir mechanically to form ANF / mixture.

[0044] Further preferably but not limiting, the nano titanium dioxide particles are rutile crystal type, and the nano titanium dioxide particle size is 5-20 nanometers, mass fraction 10-20 wt%, mechanical stirring time More preferably, the nano titanium dioxide particle size 5-10 nanometers, mass fraction 15-20 wt%, mechanical stirring time 0.75-1 hour.

[0045] It is worth noting that titanium dioxide particles have the ability to absorb high-energy particle rays. Adding them to polyimide films can effectively reduce the impact of corona aging, greatly reduce the surface roughness of the film after aging, and the addition of nano-titanium dioxide greatly improves the thermal aging resistance of MPIA materials. The present invention further recognizes that if reducing the impact of corona aging is the focus of the modification, using nano-titanium dioxide particles as fillers is a better choice.

[0046] At the same time, the prior art does not strictly control the particle size and crystal form of titanium dioxide, and after modification with dopamine and γ-aminopropyltriethoxysilane, the preparation process is cumbersome and the recyclability cannot be guaranteed. As a result, the service life of the insulating material produced and the anti-aging ability provided by the embodiments of the present invention cannot be guaranteed. As another outstanding substantial feature of the present invention, the present invention explicitly uses rutile crystal titanium dioxide particles with a particle size of 5-20 nanometers as inorganic fillers, which ensures the excellent insulation strength and mechanical strength of the prepared MPIA insulating material, and does not need to be directly added after modification. The preparation process is simple and easy to recycle. The prepared MPIA insulating material has extremely strong resistance to corona aging.

[0047] It is further worth noting that, compared with the prior art where inorganic fillers are only deposited on the surface of the insulating material and cannot effectively modify the interior, and the adhesion of the inorganic fillers and the durability of the insulating material cannot be guaranteed, as a technical feature inseparable from step 2.1, the prepared MPIA insulating material uses nanoscale MPIA staple fibers as a substrate, has a smooth surface and a honeycomb-like dense and uniform interface, and titanium dioxide particles are evenly distributed inside the insulating material. The prepared MPIA insulating material has a uniform internal structure without obvious defects, and thus the prepared MPIA insulating material has excellent wear resistance and service life.

[0048] Step 2.3: The ANF / The mixture is applied on the coating machine to set the coating thickness Coating.

[0049] Further preferably but not limiting, in step 2.3, the coating thickness is The coating thickness is 0.8-1.2 mm and the size is 10 cm × 15 cm. More preferably, the coating thickness is 0.8-1 mm.

[0050] Step 2.4: The ANF / The film is left to stand for a set period of time. Place in deionized water to reduce and form ANF / Aerogel.

[0051] Further preferably but not limiting, in step 2.4, the time of standing in deionized water is More preferably, the standing time is 10-15 hours. 13-15 hours.

[0052] Step 2.5: The ANF / Aerogel is dried at a set temperature and drying time Drying is carried out and the hot pressing temperature is set , hot pressing pressure and heat pressing time By hot pressing, recyclable and corona aging resistant MPIA insulation material can be obtained.

[0053] Further preferably but not limiting, in step 2.5, the drying temperature is 60-100℃, drying time 0.5-1 hour, hot pressing temperature 160-200℃, hot pressing pressure 15-20 MPa, hot pressing time 1-2 minutes, thickness after hot pressing More preferably, the drying temperature 80-100℃, drying time 0.75-1 hour, hot pressing temperature 180-200℃, pressure 18-20 MPa, hot pressing time 1.5-2 minutes, thickness after hot pressing 0.08-0.1 mm.

[0054] It is worth noting that in the prior art, there is no hot pressing operation on the insulating material after molding, and the overall structure is relatively loose. As another outstanding substantial feature of the present invention, the present invention proposes that the insulating material is fully hot pressed after drying to make the structure dense. After hot pressing, the surface of the insulating material is smooth and pure white, and the thickness is 0.08-0.20 mm.

[0055] Further preferably but not limiting, Example 2 provides an equation for quickly designing the process parameters of the preparation method, which is expressed as the following formula:

[0056] Where: Indicates the thickness after hot pressing, that is, the thickness of the prepared insulating material. Indicates the coating thickness; Indicates the particle size of nano titanium dioxide. represents the nanoscale MPIA staple fiber diameter, Indicates the hole diameter of the honeycomb porous structure at the interface of the insulating material; Indicates the thermal pressure, Indicates standard atmospheric pressure; is the deprotonation temperature, Indicates room temperature; represents the deprotonation time, Indicates natural day time, i.e. 24 hours; represents the concentration of ANF, represents the concentration of LiCl, represents a natural constant; and They represent adjustment constants respectively and are debugged according to the production equipment.

[0057] Step 2.6: The insulating material obtained in step 2.5 is cut according to the stator slot type, winding size and insulation requirements of the motor, and prepared into slot body insulation and inter-winding insulation.

[0058] Further preferably but not restrictively, the slot body insulation is consistent with the shape of the inner wall of the stator slot and extends toward the center of the slot at the slot opening. The inter-winding insulation includes a longitudinal beam and a cross beam extending from the longitudinal beam to both sides. The cross beam at the bottom of the slot is arc-shaped and abuts against the slot body insulation at the bottom of the slot. The cross beam at the slot opening closes the slot and overlaps with the slot body insulation at the slot opening.

[0059] Step 3: Insert the prepared slot insulation into the stator slot, ensuring that the insulation paper completely covers the slot wall and leaves enough margin; and insert inter-winding insulation between different layers of the winding to prevent inter-layer short circuit.

[0060] Preferably, but not restrictively, glue or tape is used to fix the slot body insulation in the slot to ensure that it does not shift or fall off; and the edges of the insulating paper are folded or trimmed neatly to avoid burrs or warping; tools are used to compact the insulation between the windings to ensure that it fits tightly with the windings.

[0061] Step 4: Install the rotor core, permanent magnets or windings, perform dynamic balancing tests, and install other structures to complete the assembly.

[0062] Preferably, but not restrictively, the rotor core is fixed on the shaft to ensure that it is accurately and firmly positioned; for permanent magnet motors, the permanent magnets are fixed on the rotor core; for wound rotors, the rotor windings are embedded in the rotor slots; and the rotor is dynamically balanced to ensure that it does not produce excessive vibration when rotating at high speed.

[0063] Fix the end cover to the casing and ensure that it fits tightly with the casing; for motors that need cooling, install fans and wind shields to ensure that they operate normally; fix the junction box to the casing and connect the leads of the stator winding.

[0064] As a manufacturing method of an environmentally friendly motor resistant to corona aging provided by the present invention, the preparation process is greatly simplified compared with the prior art, and closed-loop recycling is achieved. Specifically, the recovery of insulating materials in the prior art requires the use of a dissolving solution to deprotonate both sides of the insulating material, and then the deprotonated surface is treated with an enhanced solution. The process of protonation and regeneration of the surface is time-consuming, and it is difficult to achieve efficient and green closed-loop recycling. The substrate and inorganic filler of the insulating material prepared by this process are unevenly distributed. The surface of the insulating material treated with a dissolving solution is a nanostructure, while the interface is a micron structure, and the inorganic filler is only distributed in the nanostructure of the surface, which is difficult to effectively modify the inside of the insulating material. The present invention, on the other hand, directly uses MPIA staple fibers as a substrate to prepare the stock solution and apply a film. The substrate is a uniform nanoscale structure, and the inorganic filler is evenly distributed therein with sufficient mechanical stirring, and has a smooth surface and a honeycomb-like, dense and uniform interface, and titanium dioxide particles are evenly distributed inside the insulating material. After corona aging under an extremely non-uniform DC strong electric field, the prepared renewable insulating material still maintains various properties at the existing technical level, and has a strong anti-aging ability provided by the embodiment of the present invention. The overall process can be quickly prepared in large quantities and achieve efficient and green closed-loop recycling, and the recycled insulating material completely retains the performance of the existing insulating material.

[0065] Embodiment 3 of the present invention provides a method for recycling an environmentally friendly motor resistant to corona aging as described in Embodiment 1, comprising the following steps: Step 1: disassemble the environmentally friendly motor to obtain windings, magnetic components and insulation structures; Step 2: Crush and separate the insulating structure, separate the metal impurities in the insulating structure by screening, magnetic separation and other methods, and re-introduce the separated insulating structure components into the insulating material preparation process to complete the regeneration of the insulating material.

[0066] Preferably, but not limited to, the recyclable corona aging resistant MPIA insulating material is heated in a DMAc / LiCl system at a set deprotonation temperature and deprotonation time Deprotonation is performed to form ANF / Suspension; The obtained ANF / The mixture is applied on the coating machine to set the coating thickness Coating film; The obtained ANF / The film is left to stand for a set period of time. Place in deionized water to reduce and form ANF / Aerogel; The obtained ANF / Aerogel is dried at a set temperature and drying time Drying is carried out and the hot pressing temperature is set , hot pressing pressure and heat pressing time Hot pressing is performed to complete the chemical recycling of MPIA insulation materials.

[0067] It is worth noting that, as a prominent substantive feature of the present invention and a significant improvement over the prior art, after adopting the recycling method, the recycling period is 20-30 hours, and the mass recovery rate is as high as 92-97%. The insulation performance, mechanical properties, and dielectric properties of the recycled insulating material can fully retain the prior art level.

[0068] Step 3: Recycle the windings, magnetic components and other structures according to the recycling processes of metal materials and magnetic materials respectively.

[0069] In order to more clearly introduce the outstanding essential features of the present invention and the significant progress it brings to the prior art, multiple application examples of implementing the present invention are introduced below.

[0070] Application Example 1 According to the manufacturing method of an environmentally friendly motor with anti-corona aging provided in Example 2, an insulating material is prepared, specifically comprising: taking 45 mL of DMAc, 1.2 g of LiCl, and 3 g of MPIA staple fibers, respectively, deprotonating at 140° C. for 6 hours to prepare a nano-scale MPIA staple fiber solution, adding 0.75 g of ground nano-titanium dioxide to one of the two stock solutions, and mechanically stirring at room temperature for 1 hour, coating the two stock solutions on a coating machine, respectively, with a coating thickness of 1 mm, and standing in deionized water for 10 hours to obtain pure ANF aerogel and ANF / The two aerogels were dried at 80 °C for 30 min and hot pressed at 200 °C and 20 MPa for 2 min to obtain pure ANF insulating material and ANF / Composite insulating material, take 5 cm × 5 cm samples of each of the two insulating materials, and use a multi-needle plate electrode to perform aging experiments on the two samples. The aging voltage is 10 kV, the aging time is 20 hours, and the distance between the needle tip and the sample is 1 mm. The breakdown field strength and tensile strength of the two samples were tested before and after aging. The above test results are shown in Table 1. It can be seen that after aging under this condition, the decline in the two properties of the anti-aging insulating material provided by the embodiment of the present invention is less than that of the insulating material in the prior art.

[0071] Table 1 10 kV / 20h aging test data

[0072] Application Example 2 The preparation process and preparation parameters of the two samples are the same as those in Application Example 1. At the same time, aging experiments were carried out on the two samples using a multi-needle plate electrode. The aging voltage was 20 kV, the aging time was 20 hours, and the distance between the needle tip and the sample was 1 mm. The breakdown field strength and tensile strength of the two samples were tested before and after aging. The above test results are shown in Table 2. It can be seen that after aging under this condition, the decline in various properties of the anti-aging insulating material provided by the embodiment of the present invention is less than that of the insulating material in the prior art.

[0073] Table 2 20 kV / 20h aging test data

[0074] Application Example 3 The preparation process and preparation parameters of the two samples are the same as those in Application Example 1. At the same time, the two samples were subjected to aging experiments using a multi-needle plate electrode. The aging voltage was 10 kV, the aging time was 40 hours, and the distance between the needle tip and the sample was 1 mm. The breakdown field strength and tensile strength of the two samples were tested before and after aging. The above test results are shown in Table 3. It can be seen that after aging under this condition, the decline in various properties of the anti-aging insulating material provided by the embodiment of the present invention is less than that of the insulating material in the prior art.

[0075] Table 3 10 kV / 40h aging test data

[0076] Application Example 4 The preparation process and preparation parameters of the two samples are the same as those in Application Example 1. At the same time, the two samples were subjected to aging experiments using a multi-needle plate electrode. The aging voltage was 20 kV, the aging time was 40 hours, and the distance between the needle tip and the sample was 1 mm. The breakdown field strength and tensile strength of the two samples were tested before and after aging. The above test results are shown in Table 4. It can be seen that after aging under this condition, the decline in various properties of the anti-aging insulating material provided by the embodiment of the present invention is less than that of the insulating material in the prior art.

[0077] Table 4 20 kV / 40h aging test data

[0078] Application Example 5 ANF / The preparation process and preparation parameters of the composite insulating material are the same as those in Application Example 1. The sample was subjected to an aging experiment using a multi-needle plate electrode. The aging voltage was 20 kV, the aging time was 40 hours, and 3.3 g of the aged sample was collected for recycling. The mass fraction of titanium dioxide is 10 wt%, and the mass of ANF is 3 g. DMAc 45 mL and LiCl 1.2 g are taken and recycled according to the original solution concentration. The parameters in the steps of protonation, coating, deionized water standing, drying, and hot pressing are the same as those in Example 1. The breakdown field strength and tensile strength of the sample before and after recycling are tested. The above test results are shown in Table 5. After recycling, the two properties of the insulating material aged under this condition are restored to the existing technical level, and the recyclability is verified.

[0079] Table 5 20 kV / 40h aging test data before and after recycling

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents, and any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. An environmentally friendly motor with anti-corona aging, comprising: The stator core and the stator winding, the stator core is provided with stator slots for placing the stator winding, and the characteristics are: The stator core is made of multiple silicon steel sheets stacked together, and the stator winding is placed in the slots of the stator core. An insulation structure made of recyclable anti-corona insulation material is arranged in the stator slot, and the insulation structure includes: slot body insulation and inter-winding insulation, the slot body insulation is laid on the inner wall of the stator slot, and the inter-winding insulation is arranged in the space surrounded by the stator slot, and the space surrounded by the stator slot is divided into multiple parts in the direction of the cross section of the stator core, so as to separate the stator windings wound in the stator slot; The insulating material comprises: nano-scale MPIA short fibers and nano-titanium dioxide particles.

2. The environmentally friendly motor with anti-corona aging according to claim 1, characterized in that: The stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot mouth. The slot body insulation is consistent with the shape of the inner wall of the stator slot and extends to the center of the slot mouth. The insulation between windings includes longitudinal beams and cross beams extending from the longitudinal beams to both sides. The cross beam at the bottom of the slot is arc-shaped, which presses against the slot body insulation at the bottom of the slot. The cross beam at the slot mouth closes the slot mouth and overlaps with the slot body insulation at the slot mouth.

3. An environmentally friendly motor resistant to corona aging according to claim 1 or 2, characterized in that: Nano-scale MPIA staple fibers and nano-titanium dioxide particles, wherein the nano-scale MPIA staple fibers are prepared by deprotonating the MPIA staple fibers in a DMAc / LiCl system and have a diameter of 7-10 nanometers; The nano-titanium dioxide particles are rutile crystal type, have a particle size of 5-20 nanometers, a mass fraction of 10-20 wt%, and are uniformly distributed in the nano-scale MPIA staple fibers.

4. The environmentally friendly motor with anti-corona aging according to claim 3, characterized in that: The surface of the slot insulation and the insulation between windings is smooth and pure white, with a thickness of 0.08-0.20 mm, and the interface is a honeycomb porous structure with a pore diameter of 0.5-1 nanometer; After aging in a strong DC electric field for 20-40 hours, the breakdown field strength and tensile strength of the slot insulation and the insulation between the windings still retain 90-95% of the original state, and the dielectric constant and dielectric loss remain at 94-98% of the existing technical state.

5. A method for manufacturing an environmentally friendly motor that resists corona aging, used for manufacturing an environmentally friendly motor that resists corona aging according to any one of claims 1 to 4, characterized in that: The following steps are involved: A stator core including a stator slot structure is manufactured using magnetic material; An insulating material comprising nano-scale MPIA staple fibers and nano-titanium dioxide particles is prepared, and slot insulation and inter-winding insulation are prepared based on the insulating material; Insert the prepared slot insulation into the stator slot, ensuring that the insulation paper completely covers the slot wall and leaves a margin; insert interwinding insulation between different layers of the winding to prevent short circuits between layers; Install the rotor core, permanent magnets or windings, perform dynamic balancing tests, and install other structures to complete the assembly.

6. The method for manufacturing a corona aging resistant and environment-friendly motor according to claim 5, characterized in that: The method of manufacturing a stator core including a stator slot structure using a magnetic material comprises: A punching machine is used to punch the silicon steel sheet into a ring having a stator slot structure, and then annealing is performed, wherein the stator slot is a round bottom slot structure, which gradually narrows from the round bottom slot to the slot opening; Coating a layer of insulating material on the surface of the silicon steel sheet; The punched silicon steel sheets are stacked together according to the design requirements; the outer circle and inner hole of the stator core are turned, and the burrs generated during the punching and processing are removed.

7. The method for manufacturing a corona aging resistant and environment-friendly motor according to claim 5, characterized in that: The method of preparing an insulating material comprising nano-scale MPIA staple fibers and nano-titanium dioxide particles, and preparing slot insulation and inter-winding insulation based on the insulating material comprises: The MPIA staple fibers were placed in a DMAc / LiCl system and deprotonated at a set temperature to form an ANF solution; Grind the nano-titanium dioxide particles, add the ground particles into the ANF solution and stir mechanically to form ANF / mixture; The obtained ANF / The mixture is applied on the coating machine to set the coating thickness Coating film; The resulting ANF / Aerogel is dried at a set temperature and drying time Drying is carried out and the hot pressing temperature is set , hot pressing pressure and heat pressing time Applying heat pressing; The hot-pressed insulating material is cut according to the stator slot type, winding size and insulation requirements of the motor to prepare slot body insulation and inter-winding insulation.

8. The method for manufacturing a corona aging resistant and environment-friendly motor according to claim 7, characterized in that: The step of cutting the hot-pressed insulating material according to the stator slot type, winding size and insulation requirements of the motor to prepare the slot body insulation and inter-winding insulation comprises: The slot body insulation is prepared to be consistent with the shape of the inner wall of the stator slot, and extends to the center of the slot at the slot opening. The insulation between the windings includes a longitudinal beam and a cross beam extending from the longitudinal beam to both sides. The cross beam at the bottom of the slot is arc-shaped and presses against the slot body insulation at the bottom of the slot. The cross beam at the slot opening closes the slot and overlaps with the slot body insulation at the slot opening.

9. The method for manufacturing an environmentally friendly motor resistant to corona aging according to claim 7, characterized in that: Deprotonation temperature 130-150℃, time For 6-10 hours, the concentration of LiCl The concentration of ANF is 0.02-0.04 g / mL. 0.06-0.08 g / mL; Nano titanium dioxide particles are rutile crystals, and the particle size of nano titanium dioxide is 5-20 nanometers, mass fraction 10-20 wt%, mechanical stirring time 0.5-1 hour; Coating thickness 0.8-1.2 mm, size 10 cm × 15 cm; Standing time in deionized water 10-15 hours; Drying temperature 60-100℃, drying time 0.5-1 hour, hot pressing temperature 160-200℃, hot pressing pressure 15-20 MPa, hot pressing time 1-2 minutes, thickness after hot pressing 0.08-0.2 mm.

10. The method for manufacturing an environmentally friendly motor resistant to corona aging according to claim 5, characterized in that: The step of placing the MPIA staple fibers in a DMAc / LiCl system to deprotonate at a set temperature to form an ANF solution comprises: The insulating structure of the recycled environmentally friendly motor is crushed and separated, and the metal impurities in the insulating structure are separated by screening or magnetic separation to obtain MPIA staple fibers for deprotonation to form an ANF solution.

Citation Information

Patent Citations

  • Corona-resistant flat wire

    CN107347255A

  • Preparation method of high-performance aramid fiber nano mica insulation paper

    CN111926612A

  • Motor stator insulation system and pull motor stator

    CN208656535U

  • Insulating constitution of stator winding for high voltage rotary machine

    JP2001169494A

  • Insulating material containing nanocellulose

    US20140186576A1